The Effect of Bullying on Self-Esteem of Grade X Students - Yuhana Silvi; Rici Kardo; Suryadi (Global Action and Education for Society, 2026)
This research is motivated by the presence of several students who feel isolated, afraid to try new things, feel low in self-confidence, feel unappreciated, experience long-term emotional impacts such as depression, and frequently skip or miss classes. Several students who feel isolated, afraid to try new things, feel low in self-confidence, feel unappreciated, experience long-term emotional impacts such as depression, and often skip or miss classes. This study aims to determine: 1) Bullying behavior in class X at SMA Negeri 1 Ranah Batahan. 2) Self-esteem of class X students at SMA Negeri 1 Ranah Batahan. 3) Examine the Effect of Bullying on Self-esteem in Class X students at SMA Negeri 1 Ranah Batahan. This study used a quantitative research method using simple linear regression analysis. The population was 75 students, with a total sampling technique. The instrument used in this study was a questionnaire. Data analysis in this study used percentages and simple linear regression. The results of this study indicate: 1) Bullying among 10th-grade students at SMA Negeri 1 Ranah Batahan is in the high category. 2) Self-esteem among 10th-grade students at SMA Negeri 1 Ranah Batahan is in the low category. 3) Bullying has a 9% effect on 10th-grade students' self-esteem. The results indicate that bullying has a negative effect on self-esteem in 10th-grade students at SMA Negeri 1 Ranah Batahan, with a very low coefficient of 9%. The higher the level of bullying, the lower the students' self-esteem. This study shows that students who experience high levels of bullying tend to have low self-esteem. Therefore, efforts are needed to address bullying in students to improve their self-esteem. This study is recommended to principals, guidance counselors, and students to prevent bullying and improve their self-esteem.